Persepsi Generasi Z terhadap Efektivitas Aktivisme Digital sebagai Bentuk Partisipasi Sosial - Indira Nazwa Fazrina; Desy Safitri; Sujarwo Sujarwo (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The advancement of digital technology has transformed the nature of social participation, particularly among Generation Z, who were raised in a digital ecosystem. This study aims to examine Generation Z's perceptions of the effectiveness of digital activism as a form of contemporary social participation. Using a literature review method, the study analyzes various academic sources to explore the dynamics of digital activism within the context of digital natives. The findings reveal that Generation Z perceives digital activism as an effective tool to express opinions, raise public awareness, and foster solidarity. Digital activism offers accessibility, broad reach, and flexibility in conveying social aspirations. However, challenges such as slacktivism and misinformation remain significant barriers. These findings imply the need for strategic approaches to optimize digital activism as a sustainable instrument for social change.